Outcome of Ureteroscopy (URS) in Paediatric Age at Tertiary Care Hospital (Medical Forum Monthly, 2024)
Study Design: Cross sectional study. Place and Duration of Study: This study was conducted at the Tertiary Care Hospital of Sind PMCH Nawabshah from September 2016 to September 2018. Materials and Methods: Total 30 patients of middle and lower uretreic stones were admitted through OPD of Urology Department for this study. They were optimized accordingly and selected for the procedure of URS. Stones were removed through URS. Stone size and stone free rate was assessed. Results: A total of 30 patients were included in this study. There were 18(60%) males and 12(40%) females. Sex difference was found. Males were more affected than females. Age ranged from 2 to 10 years. 10 (33.33) patients had stone in middle ureter and 20(66.66%) had in lower ureter. The size of stones was different also. In middle ureter, size of single stones was found from 3 mm to 7 mm and in multiple stones, it was 8 mm to 10 mm. in lower ureter, the size of the stones were from 4mm to 14mm Conclusion: It can be summed up that ureteroscopy is the best minimally invasive procedure for children with least complications and recurrence.